How to Become an EU Citizen: The Acquisition of Citizenship via Naturalization - Clara Albrecht; Yvonne Giesing; Daria Schaller (CESifo Forum, 2020)
Migration to and within the European Union has led to a steadily rising number of foreign-born citizens living in EU member states. The naturalization of migrants therefore plays a prominent role in national integration policies. In this article we give an overview of key naturalization figures and facts in EU15 countries and Poland. We compare naturalization numbers and rates and describe the legal regulations for the acquisition of citizenship. We then discuss the controversial case of investor citizenship and conclude by providing evi-dence for the benefits of a facilitated access to citizenship.
Keywords: 330